PEMBERIAN MP-ASI PADA USIA DINI MENYEBABKAN RISIKO GANGGUAN PENCERNAAN PADA BAYI - Meila Maulidina Eka Putri; Nur Afni Aprillia; Muhammad Rifqi Muzayyan; Imam Gozali; Aufar Fadlul Hady (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Exclusive breastfeeding during the first six months of life is essential for infant health and development. However, early introduction of complementary feeding (MP-ASI) before six months of age is still commonly practiced and may increase the risk of digestive disorders. This study aimed to describe early complementary feeding practices and their effects on infant digestive health. A qualitative descriptive approach was employed, conducted at the Village Maternity Post (Polindes) of Grujugan Village from December to January 2025, with mothers of infants and health workers selected through purposive sampling. The results indicate that early complementary feeding is associated with digestive problems such as diarrhea and constipation due to the immaturity of the infant digestive system, as well as cultural influences and parental misconceptions. Therefore, exclusive breastfeeding and age-appropriate complementary feeding are crucial to support optimal infant growth and development.